2021
DOI: 10.1111/ajco.13726
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of preserving spontaneous breathing non‐intubation anesthesia in thoracoscopic surgery for lung cancer under ERAS concept

Abstract: Objective: To explore the safety and feasibility of thoracoscopic surgery in patients with lung cancer under non-intubation anesthesia, and to evaluate the advantages of the non-intubation anesthesia compared with intubation anesthesia on enhanced recovery after surgery (ERAS). Methods: A retrospective cohort study was conducted in which 100 patients who underwent thoracoscopic lung cancer surgery from January 2020 to February 2021 in the Department of Thoracic Surgery of the First Affiliated Hospital of Sooch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It offers advantages over intubated anesthesia, including reduced healthcare costs. [4] Table 1 Case report timeline.…”
Section: Discussionmentioning
confidence: 99%
“…It offers advantages over intubated anesthesia, including reduced healthcare costs. [4] Table 1 Case report timeline.…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity can not only reduce the incidence of certain types of cancer, such as lung cancer but also improve the survival rates and quality of life of cancer patients. [ 6 , 7 ] Nutrition management is also a crucial component of cancer treatment, and appropriate nutritional support can help patients maintain the necessary energy intake. Studies have shown that an intervention model combining nutrition and physical exercise is most effective in the pre-cachexia stage and can also enhance immunity, thereby supporting the rehabilitation process of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some recommendations have been developed for the ERAS guidelines in recent years to ensure that patients receive the best possible care 18 . There have been widely applied in a variety of surgical procedures, including gynecological oncologic surgery 19 , thoracic tumor surgery 20 , and urologic cancer surgery 21 23 . PCNL can also be surgically treated using ERAS.…”
Section: Introductionmentioning
confidence: 99%